Roles of CaMKIIβ in the neurotoxicity induced by ropivacaine hydrochloride in dorsal root ganglion - Xianjie Wen; Yiqun Li; Xingqing Liu; Can Sun; Jinbing Lin; Wenli Zhang; Yabin Wu; Xiaoping Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Neurotoxicity of local anesthetics is often reported in the clinic, more and more people pay attention to them. CaMKIIβ, a subtype of CaMKII, is detected in the central nervous system. Previous study found that CaMKIIβ mRNA are up-regulated in DRG neurons treated with ropivacaine hydrochloride, as well as inhibition of Cav3.2 and Cav3.3 expression can improve the local anesthetics neurotoxicity. In this study, we observed the effect of CaMKIIβ on neurotoxicity injury induced by ropivacaine hydrochloride with DRG cell in vitro. We first constructed the pAd-shRNA-CaMKIIβ-DRG to inhibit CaMKIIβ mRNA expression and detected the cell viability, cell apoptosis rate, CaMKIIβ, Cav3.2 and Cav3.3 expression. The results showed that ropivacaine hydrochloride caused the DRG cell injury with cell viability decreased and cell apoptosis rate increased, CaMKIIβ, Cav3.2 and Cav3.3 expression up-regulated. Interestingly, inhibition of CaMKIIβ expression protected the DRG cell from the neurotoxicity injury induced by ropivacaine hydrochloride, increased the cell viability and decreased the apoptosis rate, as well as inhibition of CaMKIIβ expression down-regulated Cav3.2 and Cav3.3 expression. In other words, CaMKIIβ is involved with the DRG injury induced by ropivacaine hydrochloride. Inhibition CaMKIIβ expression improved DRG injury, increased the cell viability and decreased cell apoptosis rate.